HISTOLOGICAL FEATURES OF BONE MARROW CELLS UNDER THE ANTIGENIC EFFECT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The bone marrow in the adult body is a universal hematopoietic central organ of B-lymphopoiesis. Therefore, one of the reactions of the bone marrow to antigenic effects is a reaction from lymphopoiesis. With salmonella exposure, activation of lymphopoiesis in the bone marrow is accompanied by parallel pronounced absolute and relative lymphocytosis.